Characterization of SiOx/HfOx Bilayer Resistive-Switching Memory Devices. (26th April 2016) - Chen, Ying-Chen; Chang, Yao-Feng; Wu, Xiaohan; Guo, Meiqi; Fowler, Burt; Zhou, Fei; Pan, Chih-Hung; Chang, Ting-Chang; Lee, Jack C.
Abstract : Oxide based resistive switching memory (ReRAM or RRAM) are the promising candidates for future non-volatile memory due to its fast programing, low power operation, and scalability. Among them, SiOx single layer resistive switching (RS) devices have been widely studied and characterized. The SiOx single layer resistive memory has excellent compatibility to CMOS fabrication process. However, it can only be programmed under the vacuum or non-oxidized ambient. Also, previous results reported on SiOx -based memristors indicate that the electroforming and programming voltages are relatively high, especially for low-power applications. In this work, by using SiOx /HfOx stacked structure, we have developed a low-voltage operation (< 2V) for SiOx -based ReRAM. The results show that with HfOx (3nm) on bottom, the metal-insulator-semiconductor (MIS) structures exhibit resistive switching at low voltage (< 2V) and operation in air atmosphere. The added hafnium layer is believed to provide a source to proton exchange reaction with conduction bandgap offset reduction for low-voltage (< 2V) RS. Furthermore, we have studied single HfOx -based MIS devices which exhibit bipolar-type resistive switching behaviors with small memory window. Clearly, SiOx /HfOx stacking optimization not only maintains the RS behaviors even in air environment without any programming window degradation, but also reduces the switching voltage below 2V.